The use of ratings of perceived exertion in children and adolescents: A scoping review - Kasai, D.; Parfitt, G.; Tarca, B.; Eston, R.; Tsiros, M. D. (Sports Medicine, 2021)
In adults, ratings of perceived exertion (RPE) can be used to predict maximal oxygen uptake, estimate time to exhaustion, assess internal training load and regulate exercise intensity. However, the utility of RPE in children is less researched and therefore, warrants investigation. The purpose of this scoping review is to map out the literature around the application of RPE specifically during aerobic exercise in paediatric populations. Seven bibliographic databases were systematically searched. Grey literature searching and pearling of references were also conducted. To be included for the review, studies were required to comply with the following: (1) participants aged = 18years asymptomatic of any injuries, disabilities or illnesses; (2) applied RPE in aerobic exercise, testing and/or training; (3) included at least one measure of exercise intensity; and (4) be available in English. The search identified 22 eligible studies that examined the application of RPE in children. These studies involved a total of 718 participants across ten different countries. Nine different types of RPE scales were employed. Overall, the application of RPE in paediatric populations can be classified into three distinct themes: prediction of cardiorespiratory fitness/performance, monitoring internal training loads, and regulation of exercise intensity. The utility of RPE in paediatric populations remains unclear due to the small body of available research and inconsistencies between studies. However, findings from the included studies in this scoping review may show promise. Further research focussing on child-specific RPE scales across various sports, subgroups, and in field-based settings is needed. Key Points Ratings of perceived exertion has been commonly used to assess cardiorespiratory fitness and changes in performance, monitor training load and regulate exercise intensity in children and adolescents. In the context of aerobic exercise, the utility of ratings of perceived exertion in children and adolescents remains unclear due to the small body of available research and inconsistencies between studies.